2022
DOI: 10.1177/03611981221090943
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Crash Risk Using a Multi-Level Random Parameter Binary Logit Model: Application to Naturalistic Driving Study Data

Abstract: This study presents a framework to employ naturalistic driving study (NDS) data to understand and predict crash risk at a disaggregate trip level accommodating for the influence of trip characteristics (such as trip distance, trip proportion by speed limit, trip proportion on urban/rural facilities) in addition to the traditional crash factors. Recognizing the rarity of crash occurrence in NDS data, the research employs a matched case-control approach for preparing the estimation sample. The study also conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The objective was to check whether the stochasticity embedded in the RAD generation process will be consistent for different random seed of data generated from the tool. To achieve this, the parameter estimate from the NB models for each dataset was examined using the revised Wald test statistics created by Hoover et al ( 28 ) as shown below.…”
Section: A Brief Overview Of the Rad Generation Processmentioning
confidence: 99%
“…The objective was to check whether the stochasticity embedded in the RAD generation process will be consistent for different random seed of data generated from the tool. To achieve this, the parameter estimate from the NB models for each dataset was examined using the revised Wald test statistics created by Hoover et al ( 28 ) as shown below.…”
Section: A Brief Overview Of the Rad Generation Processmentioning
confidence: 99%